The Influence Of Using Manipulative Media To Learning Outcomes To Mathematics Of Grade VB Elementary School Student In Banjar Kertahayu Way Pengubuan District - Vira Fahrena Agiyusera; Rahayu Soraya; Qomario Qomario; Agus Riyanto (SEMAR Journal : Educational Studies, 2022)
This study aims to determine the effect of the use of manipulative media on the mathematics learning outcomes of class VB students at SD Negeri 3 Banjar Kertahayu, Way Pengubuan District. The problem in this research is the low mathematics learning outcomes of class VB SD Negeri 3 Banjar Kertahayu, Way Pengubuan District. The method used in this research is quantitative with the type of pre-experimental research one group pretest-posttest design which is used to determine the effect of a treatment on research subjects. The data of this study were obtained from the pretest and post-test scores, with the instrument in the form of multiple-choice questions of as many as 15 questions. The results of hypothesis testing obtained t count t table that is 6.482 2.056 with a Significant level of 0.000 0.05, then Ha is accepted and Ho is rejected. This means that there is a significant effect of using manipulative media on the mathematics learning outcomes of class VB students at SD Negeri 3 Banjar Kertahayu, Way Pengubuan District.